Behavior of paraneoplastic dermatoses in cancer patients. Cienfuegos, 2016-2017 - Daymí Martínez Rodríguez; Elizabet Fernández López; Adialys Acosta Rodríguez (Medisur)
Background: Paraneoplastic dermatoses are rare, and about them there are no previous studies in the Cienfuegos province. The timely diagnosis of a possible internal neoplasm sometimes depends on its correct recognition. Objective: to describe the behavior of paraneoplastic dermatoses in cancer patients. Methods: descriptive study, carried out in patients with malignant neoplasms, treated from June 2016 to December 2017, at the Dr. Gustavo Aldereguía Lima Hospital, in Cienfuegos. Fifty-nine patients with paraneoplastic dermatosis were included, for which the type of dermatosis, time of appearance and its association with each type of neoplasia were analyzed. The information was obtained through the clinical dermatological examination and the medical records. Results: 17 types of paraneoplastic dermatoses were identified, highlighting the Leser Trélat sign (21.0%), followed by Sweet's syndrome (16.1%) and pyoderma gangrenosum (11.3%). In 25 (42.4%) patients these were detected before the diagnosis of neoplasms, among which lymphoma (86.7%) was the most representative, followed by colon and breast neoplasms, although they were also associated with Syndrome of Sweet and a pyoderma gangrenosum. Conclusion: Recognizing the characteristic lesions of paraneoplastic dermatoses facilitates the early detection of a hidden cancer, whose own manifestations would probably appear months later, even years.